2023
DOI: 10.1093/eurheartj/ehad118
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation for heart failure: ‘Cinderella’ or evidence-based pillar of care?

Abstract: Cardiac rehabilitation remains the ‘Cinderella’ of treatments for heart failure. This state-of-the-art review provides a contemporary update on the evidence base, clinical guidance, and status of cardiac rehabilitation delivery for patients with heart failure. Given that cardiac rehabilitation participation results in important improvements in patient outcomes, including health-related quality of life, this review argues that an exercise-based rehabilitation is a key pillar of heart failure management alongsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 88 publications
0
30
0
Order By: Relevance
“…9,10 In addition, the demanding intensity of the exercises, logistical issues such as transportation difficulties and inconvenient scheduling, and individual time constraints contribute to lower adherence rates. 11,12 In addition, these programs often fail to induce sustained behavioral change, resulting in their effect being frequently short-term. 13 Lifestyle PA interventions have emerged as an alternative approach.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In addition, the demanding intensity of the exercises, logistical issues such as transportation difficulties and inconvenient scheduling, and individual time constraints contribute to lower adherence rates. 11,12 In addition, these programs often fail to induce sustained behavioral change, resulting in their effect being frequently short-term. 13 Lifestyle PA interventions have emerged as an alternative approach.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing recognition, not only of the need to reduce the risk of clinical events and improve survival of HF patients, but also to optimize HRQoL, underscores the importance of rehabilitation 54,55 . As proposed by a recent state of the art review, evidence for ExCR, supports its place as a ‘fifth pillar’ of HF management and alongside the four classes of drugs, that is, angiotensin receptor–neprilysin inhibitors, beta‐blockers, mineralocorticoid receptor antagonists, and sodium–glucose cotransporter 2 inhibitors 9 . Whilst this review found the patient characteristics to be broadly similar across trials, irrespective of the mode of delivery, given their less intensive supervision, patients should be carefully selected for home‐based (and digitally supported) programmes.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 As proposed by a recent state of the art review, evidence for ExCR, supports its place as a 'fifth pillar' of HF management and alongside the four classes of drugs, that is, angiotensin receptor-neprilysin inhibitors, beta-blockers, mineralocorticoid receptor antagonists, and sodium-glucose cotransporter 2 inhibitors. 9 Whilst this review found the patient characteristics to be broadly similar across trials, irrespective of the mode of delivery, given their less intensive supervision, patients should be carefully selected for home-based (and digitally supported) programmes. The scientific statement from the American Association of Cardiovascular and Pulmonary Rehabilitation, the American Heart Association, and the American College of Cardiology recommend the use of home-based models, should be limited to patients who are clinically stable, at low to moderate risk, and who cannot attend a traditional supervised centre-based programme.…”
Section: Implications For Clinical Practice and Future Researchmentioning
confidence: 94%
See 2 more Smart Citations